2021
DOI: 10.14202/vetworld.2021.2002-2008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, electrolytic, and cardiovascular evaluations in cats with urethral obstruction

Abstract: Background and Aim: Urethral obstruction (UO) is a common condition in feline medicine. Severe acid-base and electrolyte disorders promote relevant electrocardiographic changes in these animals. Cardiac biomarkers such as cardiac troponin I have been shown to be useful in identifying cats with myocardial disease, but it has not been investigated whether UO leads to myocardial damages. This study aimed to evaluate biochemical changes, electrocardiographic findings, troponin I measurements, and electrolyte distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…8). Ventricular tachycardia in hyperkalaemia was previously reported by Tag and Day (2008) and Canei et al (2021). As the serum potassium concentration increased, there was a depression of the sino-atrial node, which results in a junctional or ventricular rhythm.…”
Section: Resultsmentioning
confidence: 69%
“…8). Ventricular tachycardia in hyperkalaemia was previously reported by Tag and Day (2008) and Canei et al (2021). As the serum potassium concentration increased, there was a depression of the sino-atrial node, which results in a junctional or ventricular rhythm.…”
Section: Resultsmentioning
confidence: 69%
“…Hyperkalemia may be significant in cases of UO because of metabolic acidosis and tissue catabolism [ 21 ]. As previously suggested, the severity of electrolyte abnormalities aggravates the patient's clinical status [ 28 ]. The present study observed a moderate positive correlation between the clinical score and hyperkalemia.…”
Section: Discussionmentioning
confidence: 98%
“…A UO may lead to metabolic acidosis caused by the retention of metabolic acids, HCO 3 − consumption to stabilize the plasma pH, production of lactate associated with hypovolemia, hypoxia, and reduction in HCO 3 − tubular conservation during the post-obstructive period [ 21 28 ]. Therefore, the lack of correlation between the HCO 3 − and SDMA values may be explained, in part, by the distinct mechanisms through which these two biomarkers change during renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em casos mais graves, pode ocorrer instabilidade cardiovascular e azotemia. Vale ressaltar a importância da atenção à bradiarritmia causada pela hipercalemia, o que caracteriza esse paciente como um caso emergencial que requer atendimento imediato (Canei et al, 2021).…”
Section: Pubvetunclassified